Bioactive components, in vitro digestibility, microstructure and application of soybean residue (okara): a review. Issue 1 (6th February 2020) - Kamble, Dinkar B.; Rani, Savita
Abstract: Okara is a by‐product of soymilk production with a rich nutritional profile, particularly in proteins, fibers, lipids, and bioactive components. Okara has the potential for value‐added production and utilization—choices that, at the same time, deliver on the promise of increased economic advantages along with a reduction in environmental pollution. Research on bioactive constituents, in vitro digestibility and structural aspects (microstructure and infrared spectroscopy) suggests its potential as an ingredient with high bioactive components and digestibility score, along with varied structural strength, which may be of great importance to the food industry while developing new products with okara integration. Further, various food formulations made from the addition of okara flour also suggested the potential of this low‐cost waste ingredient to enhance the nutritional value and address the various health‐related issues such as obesity, diabetes and hyperlipidemia diseases. Therefore, this mini review summarizes the existing literature with a view to establish an extensive knowledge base for the composition and utilization of okara. In addition, structural and digestibility aspects of okara are also highlighted as they may determine the quality and acceptability of the product.